Requerimiento de lisina para pavos en crecimiento en praderas de trébol ladino - J. Bixler, Edsel; Aguilera A, Augusto; Daniels B, Ricardo; Contreras G, Ignacio (Revista Mexicana de Ciencias Pecuarias, 1964)
-